Identifier et s’identifier dans les milieux lettrés bagdadiens(ve-vie/xie xiie siècles) - Vanessa Van Renterghem (Revue des Mondes Musulmans et de la Méditerranée)
This article examines informal situations of identification: encounters with strangers, implying social identification of the unknown person and the decision whether or not to interact with the unknown person. Based on textual sources referring to Seljuk Baghdad, the article first analyses these situations, their protagonists and their stakes. Identification in this case, is not a vertical, institutional process, but a reciprocal one. The tools used for this identification process are then analysed, with special attention to signals offered by the person encountered: the name, an element whose role remains ambiguous due to the risk of manipulation, the language register and, above all, the outward appearance including clothing, headgear and even hairstyle. Self-presentation is thus considered an important element in the identification process.